Di (2-ethylhexyl) Phthalate Exposure Impairs Growth of Antral Follicle in Mice - Li, Lan; Liu, Jing-Cai; Lai, Fang-Nong; Liu, Huan-Qi; Zhang, Xi-Feng; Dyce, Paul W.; Shen, Wei; Chen, Hong (PLOS ONE, 2016)
Di (2-ethylhexyl) phthalate (DEHP) is a widely used plastic additive. As an environmental endocrine disruptor, it has been shown to be harmful to the mammalian reproductive system. Previous studies indicated that DEHP inhibited the development of mouse ovarian follicles. However, the mechanisms by which DEHP affects ovarian antral follicle development during the pre-puberty stage are poorly understand. Thus, we investigated the effects of direct DEHP exposure on antral follicle growth in pre-pubescent mice by use of intraperitoneal injection. Our results demonstrated that the percentage of large antral follicles was significantly reduced when mice were exposed to 20 or 40 μg/kg DEHP every 5 days from postnatal day 0 (0 dpp) to 15 dpp. In 20 dpp, we performed microarray of these ovaries. The microarray results indicated that mRNA levels of apoptosis related genes were increased. The mRNA levels of the apoptosis and cell proliferation (negative) related genes Apoe, Agt, Glo1 and Grina were increased after DEHP exposure. DEHP induced the differential gene expression of Hsp90ab1, Rhoa, Grina and Xdh which may play an important role in this process. In addition, TUNEL staining and immunofluorescence showed that DEHP exposure significantly increased the number of TUNEL, Caspase3 and γH2AX positive ovarian somatic cells within the mouse ovaries. Flow cytometer analyses of redox-sensitive probes showed that DEHP caused the accumulation of reactive oxygen species. Moreover, the mRNA expression of ovarian somatic cell antioxidative enzymes was down-regulated both in vivo and in vitro. In conclusion, our data here demonstrated that DEHP exposure induced oxidative stress and ovarian somatic cell apoptosis, and thus may impact antral follicle enlargement during the pre-pubertal stage in mice.